Analisis Kemampuan Motorik dan Keterampilan Motorik Futsal Terhadap Performa Bermain Futsal: Studi Deskriptif pada Siswa Ekstrakurikuler SMAN 1 Jamblang - Robby; Ikbal Gentar Alam; Ahmad Hamidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the relationship between motor ability, futsal motor skill, and futsal game performance in students participating in school futsal extracurricular activities. The study was conducted at SMAN 1 Jamblang, West Java, employing a quantitative descriptive method with a correlational design. The sample consisted of 15 male students from grades 10 and 11 who actively participated in the futsal extracurricular program. Motor ability was measured using the Barrow Motor Ability Test (composite T-score), futsal motor skill was assessed through a test battery comprising passing, dribbling, and shooting, and game performance was evaluated using the Game Performance Assessment Instrument (GPAI), covering decision-making, skill execution, and support. The Shapiro-Wilk normality test revealed that the futsal motor skill variable was not normally distributed (p = 0.018), so Spearman Rho correlation was applied. Results showed: (1) a positive and significant relationship between motor ability and futsal motor skill (rs = 0.687, p = 0.005, R² = 47.19%); (2) a positive and significant relationship between motor ability and futsal game performance (rs = 0.731, p = 0.002, R² = 53.43%); (3) a positive and significant relationship between futsal motor skill and game performance (rs = 0.677, p = 0.006, R² = 45.85%). All three correlations were categorized as strong. These findings confirm that fundamental bio-motor capacity is the primary foundation determining technical quality and game performance of high school futsal extracurricular students. Keywords: Futsal Motor Skill, Game Performance, GPAI, Motor Ability